A community enterprise : the history of the Port of Fremantle, 1897 to 1997 - Tull, Malcolm T. (Research in maritime history, 2017)
This volume concerns the history of the Australian port of Fremantle, located on the edge of Western Australia and the Indian Ocean, throughout the hundred years of frequent changes to its structure and function between 1897 and 1997. Tull's aim is to use Fremantle as a prime example of the complex network of a Port, as a community and a place of vast and varied maritime business endeavours. He seeks to erase the perception of ports as 'passive links in the international transport chain' in order to draw ports to the attention and further research of maritime historians. The chapters are arranged thematically rather than chronologically, and includes statistical appendices, a bibliography, and an index, for ease of navigation. https://global.oup.com/academic/product/9780968128824?cc=us